Profil Hormon Pertumbuhan Sapi Bali Betina Pada Tiga Tipe Lahan Pemeliharaan Di Provinsi Bali (THE GROWTH HORMONE PROFILE OF BALI CATTLE’S IN THREE TYPES OF PRESERVATION AREA IN BALI PROVINCE) - Milfa, Sri; Suwiti, Ni Ketut; Tenaya, I Wayan Masa (Buletin Veteriner Udayana; Vol. 7 No. 1 Pebruari 2015, 2015)
The objective of this study was to determine the growth hormone profile of bali cattle’s whichwas reared in three different types of preservation areas in Bali Province namely gardens, fields andcultivated lands. The sample of this study was serum taken from 78 bali cattles which spread inthose three areas. The growth hormone concentration was tested from the serum using ELISA(Enzyme Linked Immunosorbent Assay). The results showed that the highest concentration of growth hormone of bali cattle’s in gardens was 3225,19 pg/ml and the lowest was 931,17 pg/mlwith mean was 1311,38±128,4. In fields area, the highest concentration of growth hormone was1852,91 pg/ml and the lowest was 906,22 pg/ml with mean was 1185,89±41,52, and in thecultivated land, the highest concentration of growth hormone was 5044,08 pg/ml and the lowestwas 1046,83 pg/ml with mean was 1927,64±246,64. This study concluded that the profile ofgrowth hormone concentration of bali cattle’s reared in gardens, fields, and cultivated land weredifferent. The highest growth hormone concentration was found in cultivated land(1927,64±246.64) and the lowest was in fields (1185,89±41.52).
Keywords: growth hormone, bali cattle, preservation area, ELISA